LETTER SENT WITH ALL NAMES AND ADDRESSES OF COMPANIES THAT HAVE RECEIVED WORKPLACE SMOKING MATERIALS OVER THE LAST TWO AND A HALF YEARS - LYONS, JOHN (Tufts Archival Research Center, 2007)
Confidential; Memorandum from John Lyons to Susan Stuntz regarding workplace smoke materials. Discusses need to evaluate workplace based programs and proposes ideas on how to carry out such evaluations. Summarizes surveys to be conducted at clients' request pertaining to workplace based programs.